Principles of national procedural law in summary procedures and the principle of effectiveness of the European law - José Caramelo Gomes (LeXonomica, 2021)
This paper presents the limits to the applicability of national procedural rules to the enforcement of European Union law by national courts in general and the European Small Claims Procedure in particular. It discusses several Court of Justice of the European Union principles, such as the principle of the institutional and procedural autonomy of the Member States, the principle of equivalence and the principle of effectiveness and points to the probable evolution of the case-law on the value and validity of national law incompatible with the European Union law.Načela nacionalnega procesnega prava v skrajšanih postopkih in načelo učinkovitosti evropskega prava. Ta prispevek predstavlja meje uporabnosti nacionalnih postopkovnih pravil za izvajanje prava Evropske unije s strani nacionalnih sodišč na splošno in evropskega postopka v sporih majhne vrednosti v podrobnosti. Obravnava več načel Sodišča Evropske unije, kot so načelo institucionalne in procesne avtonomije držav članic, načelo enakosti in načelo učinkovitosti, prikazan pa je tudi možen razvoj sodne prakse o vrednosti in veljavnosti nacionalne zakonodaje, nezdružljive z zakonodajo Evropske unije.